Methods for testing operating characteristics of nanomaterials электронный курс - Лямина, Г. В. химик доцент Томского политехнического университета, кандидат химических наук 1974- (TPU Moodle, 2018)
The overall aim of the course is to provide students with methods for testing the performance characteristics of bulk materials and nanomaterials and learn to operate the modern equipment used for these purposes: corrosion properties, thermal properties. The course realizes by blended learning: e-course involves lectures, reading, assessments, projects, multimedia (video), teamwork, case studies, demonstrations, student-led discussions; face-to-face course involves labs, assessments of Practical skills, teamwork, demonstrations, and discussions